Organoleptic Assessment and Chemical Content of Mullet Cheese Sticks for Infectious Diseases - Siahaan, Ginta; Leni Astria; Mahdiah; Sri Heriyanto; Emi Inayah (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
Infectious diseases are a global health problem and significantly contribute to mortality rates in Indonesia, including typhoid, HIV AIDS, hepatitis, pulmonary tuberculosis, and malaria in certain areas. According to the WHO in 2022, 84.2 million people have been infected with HIV, and around 40.1 million people have died. In Indonesia, the HIV prevalence in 2021 was 36,902 cases. An appropriate nutritional diet can prevent disease progression and complications, one of which is by providing high-protein snacks from mullet such as Keibel Sticks. This study aims to evaluate the organoleptic properties and analyze the chemical quality of Keibel Sticks, including zinc, albumin, iron content, and color characteristics as an alternative snack for people with infectious diseases. A Completely Randomized Design (CRD) was used, consisting of three treatments and two repetitions. The experimental units, which consisted of formulations A, B, and C, differed in main ingredient compositions and were then organoleptically tested by 60 panelists. Data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test, and results were presented descriptively in tables. The findings showed that formulation B, consisting of 50 g of mullet fish flour, 50 g of tapioca flour, and 75 g of cheese, was the most preferred. This formulation contained 1.085 mg of zinc (0.9% RDA contribution), 3.91 g of albumin, and 0.072 g of iron (8% RDA contribution). Keibel Sticks had a light yellow-brown color, a distinctive fish aroma, a dense and crunchy texture, and a savory flavor.